2000
DOI: 10.1046/j.1464-5491.2000.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Mydriasis and glaucoma: exploding the myth. A systematic review

Abstract: Mydriasis with tropicamide alone is safe even in people with chronic glaucoma. It should be advised in all patients when thorough retinal examination is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 50 publications
2
42
0
2
Order By: Relevance
“…96 The risk of provoking an acute ACG attack with tropicamide is very low, with zero cases of ACG reported in almost 4000 dilatations. 97 However, participants judged at risk of an ACG attack were not dilated and were examined through undilated pupils.…”
Section: Ocular Health Examinationmentioning
confidence: 99%
“…96 The risk of provoking an acute ACG attack with tropicamide is very low, with zero cases of ACG reported in almost 4000 dilatations. 97 However, participants judged at risk of an ACG attack were not dilated and were examined through undilated pupils.…”
Section: Ocular Health Examinationmentioning
confidence: 99%
“…A systematic review of published research 1933-1999 found no cases of angle closure precipitated by the use of tropicamide drops alone and reported them to be safe. 7 Our study suggests that angle closure can be induced by the use of tropicamide alone.…”
Section: Discussionmentioning
confidence: 65%
“…However, mydriatic eye drops are seldom used by physicians 417;418 . In general medical practice, the most common indication for pupil dilation is screening for diabetic retinopathy, where it increases the sensitivity of screening by over 50% 417 . The possibility of inducing acute glaucoma by mydriasis is often cited by diabetologists and general physicians as a reason for not routinely dilating pupils 400 .…”
Section: When Should the Pupil Be Dilated?mentioning
confidence: 99%